Pencegahan Fraud Pada Pengelolaan Dana Organisasi: Perspektif Theory of Planed Behavior - Gumelar, Taofik Muhammad; Shauki, Elvia R. (Universitas Pendidikan Indonesia, 2020)
This study aims to analyze and evaluate factors that influence students' intention to take whistleblowing actions against fraud in managing the organization's funds as an effort to prevent fraud. Students know that fraud has occurred but were unable to report due to friendship conflicts. This study seeks to fill the reseach gap, is looking at the phenomenon of student decision making in reporting fraud on managing student funds through the whistleblowing mechanism using Theory of Planned Behavior and incorporating moral norms into it. The results indicate that students' attitudes, subjective norms, and perceived behavioral control had obstacles to support the intention to take whistleblowing actions. However, only moral norms that students trigerred the moral basis in making decision to report or not to report. Though, most of the respondents stated that they had the intention to carry out whistleblowing. Thus of the four factors that influence student intentions and behavior in conducting whistleblowing actions moral norms were the most significant factor, which means students with only a strong moral norms will whistleblowing.